2010
DOI: 10.1021/es101911v
|View full text |Cite
|
Sign up to set email alerts
|

Geomicrobiological Redox Cycling of the Transuranic Element Neptunium

Abstract: Microbial processes can affect the environmental behavior of redox sensitive radionuclides, and understanding these reactions is essential for the safe management of radioactive wastes. Neptunium, an alpha-emitting transuranic element, is of particular importance because of its long half-life, high radiotoxicity, and relatively high solubility as Np(V)O(2)(+) under oxic conditions. Here, we describe experiments to explore the biogeochemistry of Np where Np(V) was added to oxic sediment microcosms with indigeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 40 publications
(67 reference statements)
11
50
0
Order By: Relevance
“…Microbially mediated Fe(III) reduction also affects the speciation of key long-lived radionuclides such as U (21), Tc (22), and Np (23) under ambient conditions. Reduction can be enzymatic (24,25) or due to abiotic electron transfer reactions with products of microbial reduction (23,26), for example, mediated by Fe(II)-bearing minerals (5). Thus, it is critical to understand the potential for microbially mediated biocycling processes under conditions relevant to geological disposal facilities.…”
mentioning
confidence: 99%
“…Microbially mediated Fe(III) reduction also affects the speciation of key long-lived radionuclides such as U (21), Tc (22), and Np (23) under ambient conditions. Reduction can be enzymatic (24,25) or due to abiotic electron transfer reactions with products of microbial reduction (23,26), for example, mediated by Fe(II)-bearing minerals (5). Thus, it is critical to understand the potential for microbially mediated biocycling processes under conditions relevant to geological disposal facilities.…”
mentioning
confidence: 99%
“…Reoxidation of immobilized radionuclides in contaminated aquifers could occur via transport of oxygenated waters through the sediments, water table fluctuations, or disturbance of the geosphere by construction or erosion (Burke et al, 2006;Wu et al, 2007). Furthermore, reoxidation caused by nitrate, a common pollutant found at nuclear facilities, is also a potential route to radionuclide reoxidation via, for example, biologically mediated Fe(II)-oxidation coupled to NO 3 À reduction (Burke et al, 2006;Geissler et al, 2011;Morris et al, 2008;Senko et al, 2005;Wu et al, 2010;Law et al, 2010b;Law et al, 2011). Recent experimental work on sediments suggests that Tc associated with Fe(II)-bearing sediments is recalcitrant to reoxidation even though significant reoxidation of Fe(II) to Fe(III) occurs during both air and nitrate reoxidation (Burke et al, 2006;Fredrickson et al, 2009;Geissler et al, in press;Jaisi et al, 2009 .…”
mentioning
confidence: 99%
“…Furthermore, this study suggested that once Np(IV) is formed, it is surprisingly resistant to reoxidation by air or nitrate additions. These observations have significant implications for contaminated land and geological disposal scenarios in which bioreduction could enhance Np retention [44].…”
Section: Characteristics Of Neptunium and Microbial Interactionsmentioning
confidence: 86%